On the requirements for protocol conversion. - Beyers, Kirsten Julia. (University of Ottawa (Canada), 1998)
The gateways that connect networks must deal with heterogeneity in the protocols they support. One approach is to implement a protocol converter on the gateway to translate and synchronize the messages between different protocols in such a way that the required service of the common upper layer protocol is satisfied. In this thesis we explore one of the main problems of heterogeneous network interconnection at a gateway: the protocol conversion problem. The protocol conversion problem deals with the rules for message exchanges and the behavioral concerns that deal with the reconciliation between different protocol message formats, their orderings and the service they provide. This thesis provides a formulation of the protocol conversion problem in a general framework. Formal methods have been proposed for the protocol conversion problem based on a common specification model for protocols: the Communicating Finite State Machine (CFSM) model. These formal methods require that the conversion requirements be defined formally as well. There are two types of conversion requirements: protocol-level conversion requirements that specify the translation requirements and the synchronization requirements of the protocol converter in terms of peer protocol messages, and service-level conversion requirements that specify the service requirements in terms of the service primitives of the conversion system. Based on the presented formulation of the protocol conversion problem, in this thesis an approach to synthesize service-level conversion requirements is proposed. Furthermore, an approach to synthesize the protocol-level conversion requirements that capture the semantic relation between the two protocols as it is specified by the service-level conversion requirements is proposed. It is then shown that existing formal methods can be used to synthesize a protocol converter using the constructed protocol conversion requirements. (Abstract shortened by UMI.)
Keywords: Computer Science.